2008
DOI: 10.1111/j.1365-2559.2008.03186.x
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1 subcellular expression in laryngeal squamous cell carcinoma

Abstract: ANXA1 dysregulation was observed early in laryngeal carcinogenesis, in intra-epithelial neoplasms; it was not found related to prognostic parameters, such as nodal metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Moreover, kim et al proposed that PMA-induced translocation of annexin A1 to the nucleus may participate in the regulation of cell proliferation and differentiation (Kim et al, 2003). In addition, several studied have approved that nuclear translocation of annexin A1 is involved in the regulation of cellular proliferation (Alldridge & Bryant., 2003;Alves et al, 2008). Similarly, in our study, as the tumor tissues of PDAC patients with high expression of annexin A1 and weak nuclear staining showed worse prognosis and outcome, we hypothesisd that annexin A1 translocated to the nuclei may be involved in the different processes in both cytoplasm and nuclei including specific cellular functions as well as signal transduction and the regulatory effects of annexin A1 may involve both transcriptional and translational levels.…”
Section: 4707 Prognostic Significance Of Annexin A1 Expression In Pasupporting
confidence: 72%
“…Moreover, kim et al proposed that PMA-induced translocation of annexin A1 to the nucleus may participate in the regulation of cell proliferation and differentiation (Kim et al, 2003). In addition, several studied have approved that nuclear translocation of annexin A1 is involved in the regulation of cellular proliferation (Alldridge & Bryant., 2003;Alves et al, 2008). Similarly, in our study, as the tumor tissues of PDAC patients with high expression of annexin A1 and weak nuclear staining showed worse prognosis and outcome, we hypothesisd that annexin A1 translocated to the nuclei may be involved in the different processes in both cytoplasm and nuclei including specific cellular functions as well as signal transduction and the regulatory effects of annexin A1 may involve both transcriptional and translational levels.…”
Section: 4707 Prognostic Significance Of Annexin A1 Expression In Pasupporting
confidence: 72%
“…However, different members of the Annexin family proteins are either up-or downregulated in cancer tissue, so different Annexins may perform different roles in specific types of cancer (5,6). It has been demonstrated that Annexin A1 is associated with esophageal cancer and is overexpressed in laryngeal carcinoma cells; it may therefore progressively migrate from the nucleus towards the membrane during laryngeal tumorigenesis (7). By contrast, Annexin A2 is associated with breast cancer (8) and knockdown of Annexin A2 by RNA interference decreases the proliferation and invasion of breast cancer cells (9).…”
Section: Introductionmentioning
confidence: 99%
“…In tumors of the head and neck area, studies have been done evaluating the role carcinomas of the head and neck and revealing a relationship between this reduction and a lack of differentiation in the tumors [42][43][44][45]. To the best of our knowledge, the present study is the first to evaluate the expression of ANXA1 in association with HPV infection in oropharyngeal cancer, thereby demonstrating a relationship between two important and current markers for this disease.…”
Section: Discussionmentioning
confidence: 96%